Effectiveness of Principal’s Attitude towards Physical Education: The Impact of Principal's Attitude on Physical Education and Social Adjustment (Journal of Advances and Scholarly Researches in Allied Education, 2022)
It is significant that principal’s attitude’s effectiveness is measured with regard to physical education in the modern urban society for social adjustment as well as their relevancy according to the social adjustment requirement as well as contribution can be made by the principal, also for physical education class’s success, it may have greater impact. Also, attitude of principal for social adjustment with regard to a specific subject is formed through hisher instructional setting or teacher’s perception. Physical education class’s perceptions as well as physical activity attitudes are significant for understanding as they can influence an individual’s decision for beginning or continuing the physical education activity participation.